Badger setts provide thermal refugia, buffering changeable surface weather conditions. (May 2018) - Tsunoda, Marie; Newman, Chris; Buesching, Christina D.; Macdonald, David W.; Kaneko, Yayoi
Abstract: Den use can be crucial in buffering environmental conditions and especially to provide an insulated environment for raising altricial young. Through Sept-Dec 2016 we monitored temperature and humidity at 11 badger setts (burrow systems), using thermal probes inserted over 4–13 sett entrances to a depth of ca. 2 m, supplemented by continuous daily logging at one entrance per sett. Setts were cooler than exterior conditions Sept-Oct, and warmer than exterior conditions Nov-Dec. Setts cooled down when badgers left them to forage by night, and warmed up when badgers occupied them by day. Soil type and aspect also influenced sett temperature. Sett temperature did not affect the weight or body-condition of either adults or maturing cubs in autumn. However, cubs born into setts that were relatively warmer through the preceding autumn-winter were heavier in the following spring than contemporaries born in cooler setts (badgers exhibit delayed implantation), and so warmer setts might benefit early cub growth. We posit that sett quality may be important in providing badgers with a stable thermal refuge from variable weather conditions. More broadly, den use may buffer climate change effects for many fossorial carnivore species. Highlights: We monitored microclimate in 11 European badger setts (dens) with a thermal probe. Badger sett temperature was more stable than exterior conditions. Soil type, aspect, and the presence of badgers all affected sett temperature. Heavier cubs developed in warmer setts in the following spring. Den use may buffer climate change effects for many fossorial carnivore species.